The Double Kingdom Under Taharqo Studies in the History of Kush and Egypt, c. 690 - 664 BC - Pope, Jeremy W. (Brill, 2014)
The establishment of Kushite rule over Egypt during the eighth and seventh centuries BC resulted in a state of extraordinary geographic dimensions and ecological diversity, stretching from the tropics of Sudanese Nubia over 3,000 km to the Mediterranean. In The Double Kingdom under Taharqo, Jeremy Pope uses the copious documentary and archaeological evidence from Taharqo's reign to address a series of questions which have dogged study of the Twenty-Fifth Dynasty: how was it possible for one king to control all of that territory? To what extent were the Kushite pharaohs' strategies of governance influenced by the circumstances of their homeland versus the precedents of Egyptian and Libyan rule? And how did Kushite policies differ from those of their Saïte successors?